EFEKTIVITAS PAJAK BUMI BANGUNAN PERDESAAN PERKOTAAN (PBB-P2) TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KUBU RAYA - jaurino (Jurnal Akuntansi, Auditing dan Investasi, 2021)
This research was conducted at the Office of the Regional Tax and Retribution Management Agency (BPPRD), Kubu Raya Regency, West Kalimantan. research problems regarding the level of effectiveness, the level of PBB-P2 revenue contribution, the growth rate of PBB-P2 and PAD as well as the target and realization of Government PAD, the delivery system for SPPT PBB P2 to taxpayers, and the obstacles faced in efforts to increase PBB-P2 revenue in Kubu Raya Regency.The method used in this research is quantitative research methods. This research is a quantitative research with quantitative descriptive analysis techniques using the ratio of effectiveness and contribution. The data collection method used is the interview method and documentation method. The data studied were data on the target and realization of PBB-P2 revenue, data on the realization of local tax revenue and revenue from regional original revenue (PAD), and the results of interviews.The results showed that the level of effectiveness of PBB P2 revenue in 2013-2017 was quite effective with an average of 80.80%, the contribution rate of PBB P2 revenue to local tax results in 2013-2017 showed less results with an average value of 11.90 %, the contribution rate of PBB P2 revenue to Regional Original Revenue (PAD) in 2013-2017 shows very poor results with an average value of 2.01%. The obstacles to the Kubu Raya Government in optimizing PBB-P2 revenue are the lack of awareness from the public to pay PBB-P2, the existence of empty tax objects and subjects, and the far distance of taxpayers' places. Keywords: Effectiveness, PBB-P2, Regional Original Income.